Advances in the mechanism of metformin with wide-ranging effects on regulation of the intestinal microbiota - Wang, Yue; Jia, Xianxian; Cong, Bin (Frontiers in Microbiology, 2024)
Metformin is of great focus because of its high safety, low side effects, and various effects other than lowering blood sugar, such as anti-inflammation, anti-tumor, and anti-aging. Studies have shown that metformin has a modulating effect on the composition and function of the intestinal microbiota other than acting on the liver. However, the composition of microbiota is complex and varies to some extent between species and individuals, and the experimental design of each study is also different. Multiple factors present a major obstacle to better comprehending the effects of metformin on the gut microbiota. This paper reviews the regulatory effects of metformin on the gut microbiota, such as increasing the abundance of genus Akkermansia, enriching short-chain fatty acids (SCFAs)-producing bacterial genus, and regulating gene expression of certain genera. The intestinal microbiota is a large and vital ecosystem in the human body and is considered to be the equivalent of an "organ" of the human body, which is highly relevant to human health and disease status. There are a lot of evidences that the gut microbiota is responsible for metformin's widespread effects. However, there are only a few systematic studies on this mechanism, and the specific mechanism is still unclear. This paper aims to summarize the possible mechanism of metformin in relation to gut microbiota.